All sequential allotment rules are obviously strategy-proof - Arribillaga, Roberto Pablo (2021)
For division problems with single-peaked preferences (Sprumont, 1991) we show that all sequential allotment rules, identified by Barbera, Jackson and Neme (1997) as the class of strategy-proof, efficient and replacement monotonic rules, are also obviously strategy-proof. Although obvious strategy-proofness is in general more restrictive than strategy-proofness, this is not the case in this setting.